Aproveitamento Industrial do Mármore da Sequência Metavulcano-Sedimentar Marmeleiro, Rio Grande do Sul, Brasil. Dados Petrográficos e Químicos - SIVIERO, ROSEMERI SOARES; PULZ, GÊNOVA MARIA (Pesquisas em Geociências, 2001)
This study presents chemical and petrographic properties of marble of the Marmeleiro metavolcano-sedimentary sequence, Southern Brazil. This rock is characterized by 80% of the pure calcite, 48 to 53.3 wt.% of CaO, 0.32 to 0.86 wt.% of MgO and neutralizing value between 75 and 91%. The elevated loss on ignition this rock makes possible the production of considerable amounts of CaO after calcinations. These characteristics are adequated for manufacture of Portland lime, as well as for agricultural lime.